A novel screening system based on VanX‐mediated autolysis—Application to Gaussia luciferase. Issue 7 (28th January 2016) - Wu, Nan; Kamioka, Tetsuya; Kuroda, Yutaka
ABSTRACT: We report a novel bacterial screening protocol based on co‐expressing the target protein with VanX, an enzyme which mediates Escherichia coli 's autolysis and the release of the target protein into the culture medium, thereby facilitating activity measurement and screening from crude medium. This protocol as assessed with 19 Gaussia luciferase (GLuc) expressing colonies, was able to detect bioluminescence wavelength shift as small as 1.5 nm. We demonstrate the performance and versatility of this protocol by applying it to a semi‐rational search for GLuc variants with red‐shifted bioluminescence. Six GLuc's sites, F113, I114, W143, L144, A149, and F151, were randomly mutated, and for each site, 50 colonies were cultivated in 3 mL samples, from which bioluminescence was measured without purification. We identified two GLuc single mutation red‐shifted variants: W143V and L144A. Their red shifted bioluminescence and biophysical/biochemical properties were confirmed using HPLC purified variants. Biotechnol. Bioeng. 2016;113: 1413–1420. © 2015 Wiley Periodicals, Inc. Abstract : This paper reports a novel bacterial screening protocol based on co‐expressing the target protein with VanX, an enzyme which mediates Escherichia coli 's autolysis and the release of the target protein into the culture medium, thereby facilitating activity measurement and screening from crude medium. The versatility of this protocol was demonstrated by applying it to a semi‐rational search for Gaussia luciferase (GLuc) variants with redshifted bioluminescence. Two GLuc single mutation variants W143V and L144A with red‐shifted spectra were identified.